Deleterious effects of polypropylene released from paper cups on blood profile and liver tissue of Clarias gariepinus: bioremediation using Spirulina - Eid, Zainab; Mahmoud, Usama M.; Sayed, Alaa El-Din H. (Frontiers in Physiology, 2024)
Despite numerous studies on microplastics, the biological impacts of polypropylene microplastics (PP-MPs) and its toxicity on freshwater fish have yet to be fully revealed. The purpose of this research was to look at the potentially harmful effects of PP-MPs in freshwater African catfish Clarias gariepinus and bioremediation using Spirulina. After acclimatization to lab conditions, 108 fish (125±3 gm and 27±2 cm) were assigned into triplicate six experimental groups (12 fish/group), a control group, Spirulina group (SP), PP-MPs -treated groups (0.14 and 0.28 mg/l PP-MPs) and PP-MPs + Spirulina-treated groups (0.14 mg/l PP-MPs +200 mg/l SP and 0.28 mg/l PP-MPs + 200 mg/l SP) for 15 days exposure and 45 days recovery after that. The hematological parameters exhibiting significance (RBCs, Hct, Hb, and MCV) or non-significance (MCH and MCHC) either decreased with the increase of PP-MPs doses from 0.0 in the control to 0.28 mg/l red blood cells (RBCs), hematocrit (Hct), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), hemoglobin (Hb) and platelets) or increased with such increase of doses (mean corpuscular volume (MCV)). The liver enzymes activity, aspartate aminotransferase (AST), alkaline phosphatase (ALP) and alanine aminotransferase (ALT) exhibiting non-significant (P ≥ 0.05) or significant (P < 0.05) increase in (0.14 and 0.28 mg/l) PP-MPs exposed groups respectively except (ALP). Furthermore, there was significant (P < 0.05) or non-significant (P ≥ 0.05) increase in 0.14 and 0.28 mg/l PP-MPs + 200 mg/l exposed groups respectively compared to the control group and the same exposed group without Spirulina. In comparison to the control group, PP-MPs (0.14 and 0.28 mg/l) induced a significant (P < 0.05) increase in the percentage of poikilocytosis and nuclear abnormalities of RBCs. The liver tissue from fish exposed to PP-MPs exhibited various degrees of pathological changes .These results indicated that these pathological changes increased with PP-MPs concentration, suggesting that the effect of PP-MPs was dose-dependent. After 45 days of recovery under normal conditions, it was obvious that there was a significant improvement in the percentage of poikilocytosis and nuclear abnormalities of RBCs, as well as a non-significant improvements in hemato-biochemical parameters and liver tissue.